2015
DOI: 10.1016/j.apcatb.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electrode sequence on electrochemical removal of trichloroethylene from aqueous solution

Abstract: The electrode sequence in a mixed flow-through electrochemical cell is evaluated to improve the hydrodechlorination (HDC) of trichloroethylene (TCE) in aqueous solutions. In a mixed (undivided) electrochemical cell, oxygen generated at the anode competes with the transformation of target contaminants at the cathode. In this study, we evaluate the effect of placing the anode downstream from the cathode and using multiple electrodes to promote TCE reduction. Experiments with a cathode followed by an anode (C→A) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 67 publications
1
30
1
Order By: Relevance
“…Reduction via hydrodechlorination (HDC) is favorable degradation path for TCE from groundwater [23, 25, 26, 3234]. HDC occurs via a reaction of chlorinate substance with atomic hydrogen that forms at the cathodes and is the main reduction mechanism at hydrogen formation potentials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction via hydrodechlorination (HDC) is favorable degradation path for TCE from groundwater [23, 25, 26, 3234]. HDC occurs via a reaction of chlorinate substance with atomic hydrogen that forms at the cathodes and is the main reduction mechanism at hydrogen formation potentials.…”
Section: Introductionmentioning
confidence: 99%
“…The sequential oxidation and reduction processes can be utilized for the transformation of COCs and lead to the creation of less toxic by-products [27, 34, 38]. Authors previously reported that shifts between oxidation and reduction, via electrode polarity reversal, improve TCE removal [39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new system was designed to promote electrochemical reduction, which is the primary degradation mechanism of highly oxidized chemical compounds such as TCE. The design, introduced by our laboratory, adopts a flow-through cell with the cathode placed in front of the active anode with respect to the flow direction, to minimize the effect of oxygen on HDC of TCE (Rajic et al, 2014, 2015a, 2015b, 2015c). …”
Section: Introductionmentioning
confidence: 99%
“…Further, the ohmic potential is affected directly by the gap distance between the electrodes; the drop of ohmic potential is proportional to the gap distance between electrodes [156,157]. Thus, an optimized design between the cell cross section (gap distance between electrodes) and bulk flow rate velocity should be considered not only to enhance the bubble release from the electrode surface, but also the avoid having a significant voltage drop in the system.…”
Section: Nagai N Et Al 2003 [155] Found At Low Current Density Thmentioning
confidence: 99%